Application of Nishab of Zakat Profession at BAZNAS Tanah Datar Regency - Afrimaigus; Renata, Nadia (Yayasan Mitra Peduli Indonesia, 2022)
Zakat is a pillar of Islam that must be fulfilled by Muslims who have fulfilled the nishab. One of the zakat management entities in Indonesia is the National Amil Zakat Agency (BAZNAS) of Tanah Datar Regency. This study aimed to determine the standard for determining the professional zakat nishab applicable in BAZNAS Tanah Datar Regency. This study uses a qualitative descriptive method with a case study and literature study. Data sources are from interviews with the Head and Executive Head of BAZNAS Tanah Datar Regency and the Zakat Collecting Unit (UPZ) management within the Tanah Datar Regency Government. Secondary data sources came from literature and documentation. The results showed that BAZNAS Tanah Datar Regency had two professional zakat nishab standards, namely 34 gold, equivalent to 85 grams of gold, and civil servants at least group 3A.